2014
DOI: 10.1007/s11356-014-3675-0
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and size distribution of viable bioaerosols during non-haze and haze days in Beijing

Abstract: Accumulation of airborne particulate matter (PM) has profoundly affected the atmospheric environment of Beijing, China. Although studies on health risks have increased, characterization of specific factors that contribute to increased health risks remains an area of needed exploration. Chemical composition studies on PM can readily be found in the literature but researches on biological composition are still limited. In this study, the concentration and size distribution of viable airborne bacteria and fungi w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 35 publications
(46 reference statements)
4
18
1
4
Order By: Relevance
“…Here, for the first time we have captured the size-and time-resolved massive microbial level increase and structure shift events in high PM 2.5 polluted air in Beijing using a high-volume portable aerosol sampler up to 1000 L/min. Traditionally, people often use low flow rate sampler such as BioSampler (SKC, INc., flow rate=12.5 L/min) and the 4-channel PM sampler (16.7 L/min) or sometimes up to 100 L/min, but most for short time samplings(Gao et al, 2015b;Yuan et al, 2017). These samplers with low sampling rates often fail to capture rapid but transient microbial events in the air since newly bacterial aerosol dynamics could be quickly diluted by open ambient air, and such time-resolved events could also discontinue as atmospheric conditions change from the air.…”
Section: Resultsmentioning
confidence: 99%
“…Here, for the first time we have captured the size-and time-resolved massive microbial level increase and structure shift events in high PM 2.5 polluted air in Beijing using a high-volume portable aerosol sampler up to 1000 L/min. Traditionally, people often use low flow rate sampler such as BioSampler (SKC, INc., flow rate=12.5 L/min) and the 4-channel PM sampler (16.7 L/min) or sometimes up to 100 L/min, but most for short time samplings(Gao et al, 2015b;Yuan et al, 2017). These samplers with low sampling rates often fail to capture rapid but transient microbial events in the air since newly bacterial aerosol dynamics could be quickly diluted by open ambient air, and such time-resolved events could also discontinue as atmospheric conditions change from the air.…”
Section: Resultsmentioning
confidence: 99%
“…Relevant studies suggested that the bacterial community was highly variable under different PM 2.5 mass concentrations (Cao et al, 2014). Statistical analysis, e.g., correlation or multiple linear regression, indicated that PM 2.5 exhibited a negative correlation with airborne bacteria on haze days (Gandolfi et al, 2015;Gao et al, 2015), whereas in another study, Spearman correlation analysis showed that PM 2.5 exhibited a significant positive correlation with the airborne microbe concentration (Dong et al, 2016). Possibly, the inorganic and organic compounds in particulate matter (PM 2.5 ) can be available nutrients for microbial growth in air.…”
Section: Environmental Factors Shaping the Bacterial Community Structurementioning
confidence: 99%
“…Several studies have been conducted on indoor and outdoor PM concentrations related to bioaerosols and diseases (Gao et al 2014;Ha et al 2011;Jo and Seo 2005;Kim et al 2012;Tina and Barbara 2008;Zorman and Jersek 2008), but few of them combined ventilation characteristics with indoor and outdoor PM correlations on each floor of the building in Korea.…”
Section: Introductionmentioning
confidence: 99%